Focal Neuronal Gigantism: A Rare Complication of Therapeutic Radiation - Gaughen, J.R.; Bourne, T.D.; Aregawi, D.; Shah, L.M.; Schiff, D. (American Journal of Neuroradiology, 2009)
SUMMARY: Radiation therapy, a mainstay in the treatment of many brain tumors, results in a variety of well-documented acute and chronic complications. Isolated cortical damage following irradiation represents an extremely rare delayed therapeutic complication, described only twice in the medical literature. We report this rare delayed complication in a patient following treatment of a right frontal anaplastic oligodendroglioma.